Lymphocyte and dendritic cell response to a period of intensified training in young healthy humans and rodents: A systematic review and meta-analysis - Baker, Carla; Hunt, John; Piasecki, Jessica; Hough, John (Frontiers in Physiology, 2022)
Background: Intensified training coupled with sufficient recovery is required to improve athletic performance. A stress-recovery imbalance can lead to negative states of overtraining. Hormonal alterations associated with intensified training, such as blunted cortisol, may impair the immune response. Cortisol promotes the maturation and migration of dendritic cells which subsequently stimulate the T cell response. However, there are currently no clear reliable biomarkers to highlight the overtraining syndrome. This systematic review and meta- analysis examined the usefulness of immune cells in the diagnosis of negative states of overtraining. Methods: SPORTDiscus, PUBMED, Academic Search Complete, Scopus and Web of Science were searched until June 2022. Included articles reported on immune biomarkers relating to lymphocytes, dendritic cells, and cytokines before and after a period of intensified training, in humans and rodents, at rest and in response to exercise. Results: 164 full texts were screened for eligibility. Across 57 eligible studies, 16 immune biomarkers were assessed. 7 were assessed at rest and in response to a bout of exercise, and 9 assessed at rest only. Included lymphocyte markers were CD3+, CD4+ and CD8+ T cell count, NK cell count, NK Cytolytic activity, lymphocyte proliferation and CD4/CD8 ratio. Dendritic cell markers examined were CD80, CD86, and MHC II expression. Cytokines included IL-1β, IL-2, IL-10, TNF-α and IFN-γ. A period of intensified training significantly decreased resting total lymphocyte (d= -0.57, 95% CI -0.30) and CD8+ T cell counts (d= -0.37, 95% CI -0.04), and unstimulated plasma IL-1β levels (d= -0.63, 95% CI -0.17). Resting dendritic cell CD86 expression significantly increased (d= 2.18, 95% CI 4.07). All other biomarkers remained unchanged. Conclusion: Although some biomarkers alter after a period of overtraining, definitive immune biomarkers of overtraining are limited. Specifically, due to low study numbers, further investigation into the dendritic cell response in human models is required.